The Diagnostic Significance of Hemogram Indicators and Serum Markers of Inflammation in Serious Bacterial Infections in Children Under 5 Years of Age - O. S. Melnichuk; T. V. Kulichenko; N. A. Mayanskiy; A. Ye. Malakhova ("Paediatrician" Publishers LLC, 2016)
Background: Diagnosis of serious bacterial infections (SBI) in young children is a difficult task for pediatricians.Objective: Our aim was to determine regularities of the change of hemogram indicators and serum markers of inflammation for the differential diagnostics of SBI in children under the age of 5 years.Methods: The comparative retrospective study is carried out. We analyzed diagnostic characteristics of laboratory markers of SBI during the examination of 306 children with pyretic fever. We determined the number of leukocytes, neutrophils, immature granulocytes, reticulocyte hemoglobin equivalent, C-reactive protein (CRP) and procalcitonin.Results: The study of CRP content has the greatest diagnostic accuracy at differential diagnostics of SBI in children with infectious fever at the height of disease. It is established that the positive result of CRP ( 37 mg/L) increases the probability of SBI in patient from 17.6% to 70%, and the negative result (< 37 mg/L) reduces the probability of SBI to 4%.Conclusion: Cut-off values of the laboratory parameters obtained in our study can be used when assessing the post-test probability of SBI in children with infections accompanied by pyretic fever.